Ghana - Jirapa Village - CGIAR Research Program on Climate Change, Agriculture and Food Security (2010)
Pictures are from meeting with innovative farmer Joel Yiri, Jirapa Village in Ghana. He started developing his plot of land by using manure from his pigs when he realized the soil had become infertile. He is also serious about keeping a record of all input costs and revenues, meaning that he now can track looses and change crops and production techniques accordingly. Joel Yiri is also experiencing a change in rainfall patters, the rain start later every year, and stops earlier, mixed with periods of drought.